SPECT/CT imaging in breast cancer - current status and challenges - Simanek, Milan; Koranda, Pavel (Biomedical papers, 2016)
Background: The increasing incidence of breast cancer worldwide raises the importance of improving imaging techniques for disease stratification after early lesion detection. SPECT/CT imaging is now widely available but its diagnostic potential is not fully utilized for more specific purposes including breast cancer patient stratification. Methods and Results: A Pubmed search for both original and review articles related to the value of SPECT/CT in breast cancer patients and comparison to other diagnostic methods. 62 articles were found using the key words SPECT/CT, Fusion Image and Breast Cancer. Development of a new generation of SPECT/CT systems and their introduction into practice has changed the old diagnostic algorithm. The increasing importance of SPECT/CT in the detection of bone metastases is confirmed. The diagnostic accuracy of new SPECT/CT instruments in the diagnostics of bone metastases is nearly comparable to PET/CT scans. SPECT/CT is more widely available and costs less than PET. It is able not only to identify a sentinel lymph nodes in atypical localizations but also to detect sentinel lymph nodes non visualized on previous planar scans. SPECT/CT offers precise anatomic localization of sentinel lymph nodes, thereby facilitating surgery. Knowledge of precise sentinel lymph node localization can also be applied in radiotherapy. Conclusions: The role of hybrid SPECT/CT imaging in breast cancer patients is changing. It is a powerful modality for skeletal and nodal staging in breast cancer patients with important impact on therapy.
Keywords: breast neoplasms; sentinel lymph node biopsy; neoplasm metastasis; multimodal imaging; SPECT/CT